Analisis Manajemen Dalam Upacara Adat Mbaba Belo Selambar Etnik Batak Karo : Kajian Sejarah Adat Dan Budaya - Sitompul, Yulia Saftania; Saragih, Dinda Apriani; Hutauruk, Febri Ola; Harefa, Evelina; BrSimatupang, Nori Marta Marselina; Tampubolon, Flansius (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study examines the analysis of management in the traditional ceremony of Mbaba Belo Selambar, as one of the cultural traditions in the Batak Karo community. Mbaba Belo Selambar is a traditional ritual that has a deep meaning in the social structure system of the Batak Karo community. In this context, it can be explained how the concept of Mbaba Belo Selambar in the socio-cultural structure of the Batak Karo community and the values contained in the Mbaba Belo Selambar ceremony in the Batak Karo community. This study aims to examine in depth the concept of Mbaba Belo Selambar in the socio-cultural structure of the Batak Karo community and identify the values contained therein. This research method uses a qualitative approach with data collection on secondary data sources from literature studies and documents on Batak Karo cultural literature. Data collection techniques include in-depth interviews: conducting structured and semi-structured interviews with key informants of Mbaba Belo Selambar practices in various social contexts. The results of this study indicate that Mbaba Belo Selambar has a complex cultural management structure involving rakut sitelu in the Batak Karo community, including traditional elders, and local communities. This practice is managed through a mutual cooperation system that reflects the strong values of social solidarity in Karo culture. This study contributes to the understanding of the dynamics of traditional cultural management in the context of Indonesian society, especially in terms of how ethnic communities maintain and manage their cultural heritage.